Aplikasi QR Code Generator Dan QR Code Reader Menggunakan Metode Stroke Histogram - wahyu riansah (STMIK Triguna Dharma, 2021)
Quick Response Code (QR Code) is a two-dimensional image that has the ability to store data. QR Code is commonly used to store data in the form of text, be it numeric, alphanumeric, or binary code. QR Code is widely used for commercial purposes, especially in Japan, usually contains a url link to a specific address or simply text containing advertisements, promotions, and others. One of the things that is not commonly used in QR codes is inserting images into the information it stores. This can increase readers' appeal, especially for advertising, posters, and other commercial matters.This research conducted a study on the possibility of making a QR Code from text input data. Therefore an analysis is carried out on how to make the image the content of the information contained in the QR Code. The solution offered is to convert the text into another representation that can be understood by the QR Code generator and QR Code reader. Previously, the text file was converted into binary.This research also generates QR Code Generator and QR Code Reader, where the input data is in the form of text, then tested to be applied in the real world. The software implementation is done using PHP with MySQL database.